Pengaruh kesejahteraan psikologis dan dukungan sosial terhadap kesiapan kerja mahasiswa guna memperkuat kemitraan dan jaringan internasional institusi - Imro’ah, Wulidatul (Maliki Interdisciplinary Journal, 2024)
Psychological well-being and social support have an important role in shaping students’ work readiness to face challenges in the world of work and help in efforts to improve the institution’s internationalization partnerships and networks. This study aims to determine the effect of psychological well-being and social support on student work readiness in an effort to strengthen the institution’s international partnerships and networks. This research applies a quantitative approach with regression analysis and primary data type. The sampling technique applied non-probability sampling technique with purposive sampling type, so that 100 respondents were obtained. The data analysis techniques used are instrument tests, classical assumption tests, and multiple linear regression. The software used is Microsoft Excel and SPSS (Statistical Product and Service Selection) version 26. Based on the results of the analysis that has been carried out, the results show that psychological well-being has a positive and significant effect on student work readiness, as well as social support has a positive and significant effect on student work readiness. Psychological well-being and social support have an important role in shaping students’ work readiness to face challenges in the world of work and help in efforts to improve the institution’s internationalization partnerships and networks. This study aims to determine the effect of psychological well-being and social support on student work readiness in an effort to strengthen the institution’s international partnerships and networks. This research applies a quantitative approach with regression analysis and primary data type. The sampling technique applied non-probability sampling technique with purposive sampling type, so that 100 respondents were obtained. The data analysis techniques used are instrument tests, classical assumption tests, and multiple linear regression. The software used is Microsoft Excel and SPSS (Statistical Product and Service Selection) version 26. Based on the results of the analysis that has been carried out, the results show that psychological well-being has a positive and significant effect on student work readiness, as well as social support has a positive and significant effect on student work readiness. Thus, efforts to improve psychological well-being and provide social support to students as part of a strategy to improve readiness to face challenges in the job market are very important because by strengthening psychological well-being and social support, higher education institutions can make a significant contribution in preparing students to succeed in an increasingly complex and diverse work environment.